1987
DOI: 10.1007/bf00348918
|View full text |Cite
|
Sign up to set email alerts
|

CT diagnosis of lumbosacral conjoined nerve roots

Abstract: The authors report the observations derived from CT evaluation of 19 cases of lumbosacral conjoined nerve roots; 11 of these have been confirmed by lumbar myelography and/or at surgery. They conclude that CT without intrathecal metrizamide allows the recognition in most cases of the presence of conjoined nerve roots and to differentiate them from a herniated disk fragment; this is especially useful to avoid surgical damage of anomalous roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…12 Imaging studies like computerized tomography scans have reported incidences of 2%. 13,14 MRI scans are presently the most commonly used imaging modality to detect conjoined roots. [15][16][17] Various signs on routine sagittal and axial MRI scans have been described such as Kang et al sagittal shoulder sign and the axial sagittal passage sign.…”
Section: Discussionmentioning
confidence: 99%
“…12 Imaging studies like computerized tomography scans have reported incidences of 2%. 13,14 MRI scans are presently the most commonly used imaging modality to detect conjoined roots. [15][16][17] Various signs on routine sagittal and axial MRI scans have been described such as Kang et al sagittal shoulder sign and the axial sagittal passage sign.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes two separate, conjoined round structures, which can be followed in the next slices through the intervertebral foramen, can be observed. Another helpful tool is the estimation of attenuation values allowing the differentiation of denser herniated discs from dural sac structures [20]. Additionally, conjoined nerve roots are typically located close to the pedicle level in axial slices, whereas herniated discs can only be found in this location in the case of migrated disc fragments.…”
Section: Discussion: Diagnostic Methodsmentioning
confidence: 99%
“…Consisten en la agrupación de dos raíces nerviosas adyacentes contenidas en una envoltura dural común, localizada en diferentes partes de su trayecto habitual 2 . Son el tipo de anomalías más común de las raíces nerviosas; de origen congénito, asociado a la migración aberrante de las raíces nerviosas durante el periodo embrionario, sin una causa clara establecida; la incidencia según la literatura es variable, teniendo en cuenta el diagnóstico clínico, imagenológico e intraoperatorio 3,4 . Los hallazgos realizados mediante estudios imagenológicos (tomografía computarizada [TC], resonancia magnética [RM] y melografía) varían la incidencia entre el 2 y el 17%, y en estudios cadavéricos entre el 14 y 30%, siendo la localización más común en segmento L5-S1 con predomino de lateralidad izquierda [4][5][6][7] .…”
Section: Introductionunclassified